What are the attitudes, beliefs and knowledge of health care professionals about chronic fatigue syndromes and fibromyalgia : a systematic review to guide curriculum development - Reypert, Garth (Department of Public Health and Family Medicine, 2016)
Chronic Fatigue Syndrome or Myalgic Encephalomyelitis (CFS/ME) is a relatively unknown disease and is often referred to as a diagnosis of exclusion. Diagnostic tests are not available for this disease because a single empirical cause or marker has yet to be discovered. This means that diagnosis and management is almost solely based on the skill of the health care professional to notice the signs and symptoms of the disease, the subtleties of which often only come with experience. While some studies have assessed the knowledge, attitudes and beliefs of health care professionals (HCP) towards CFS/ME, none have reviewed all the studies focused on health care professionals to aide students and inexperienced professionals to avoid negative behaviours that might lead to a CFS/ME patient not being diagnosed as having CFS/ME. This review contains three parts. Part A is the protocol for the review. This will highlight the background of CFS/ME knowledge and outline the review's methodology. The review will take the form of a qualitative systematic review. Six databases will be searched with the relevant keywords and search terms outlined in the protocol. Appropriate articles will be selected based on the inclusion and exclusion criteria defined in the protocol. Part B is the literature review of the existing research available in the field of CFS/ME, the knowledge of the disease and the attitudes and beliefs of health care professionals about CFS/ME. It will provide a background for the full systematic review in Part C. This review will detail what is known about CFS/ME as a disease, report on potential causal mechanisms for CFS/ME as a disease and report on the scope of the disease in epidemiological terms. Part C is the full systematic review. It follows the previous section in the description of the background as well as outlining the methodology followed. The results of the search are then reviewed and discussed in detail.